2013
DOI: 10.1016/j.ultrasmedbio.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Fully Automatic 3-D Echocardiographic Segmentation Using B-Spline Explicit Active Surfaces: Feasibility Study and Validation in a Clinical Setting

Abstract: A novel framework to efficiently deal with three-dimensional (3-D) segmentation of challenging inhomogeneous data in real-time has been recently introduced by the authors. However, the existing framework still relied on manual initialization, which prevented taking full advantage of the computational speed of the method. In the present article, an automatic initialization scheme adapted to 3-D, echocardiographic data is proposed. Moreover, a novel segmentation functional, which explicitly takes the darker appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 32 publications
0
48
0
Order By: Relevance
“…Although generic data attachment terms can be used, such as the Chan-Vese [30] and Yezzi [31] segmentation functionals and their localized counterparts [32], the segmentation energy can be tailored for more specific applications. For instance, the darker appearance of the blood in RT3DE data can be explicitly taken into account when designing the energy to be minimized during the segmentation of RT3DE data, which improves the robustness of the method in this particular application [25]. Taking this an example, it can be shown that this energy can be directly minimized wrt.…”
Section: B-spline Explicit Active Surfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although generic data attachment terms can be used, such as the Chan-Vese [30] and Yezzi [31] segmentation functionals and their localized counterparts [32], the segmentation energy can be tailored for more specific applications. For instance, the darker appearance of the blood in RT3DE data can be explicitly taken into account when designing the energy to be minimized during the segmentation of RT3DE data, which improves the robustness of the method in this particular application [25]. Taking this an example, it can be shown that this energy can be directly minimized wrt.…”
Section: B-spline Explicit Active Surfacesmentioning
confidence: 99%
“…1. The segmentation algorithm is automatically initialized with an ellipsoid using the algorithm proposed in [25], allowing fully automatic segmentation of the left ventricle. Further details on the foundations of the BEAS framework can be found in [23].…”
Section: B-spline Explicit Active Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on echocardiograph, several different methods have been proposed to estimate the LV volumes [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%